2021
DOI: 10.1186/s13075-021-02525-8
|View full text |Cite|
|
Sign up to set email alerts
|

Denosumab alleviates intervertebral disc degeneration adjacent to lumbar fusion by inhibiting endplate osteochondral remodeling and vertebral osteoporosis in ovariectomized rats

Abstract: Background Although adjacent segmental intervertebral disc degeneration (ASDD) is one of the most common complications after lumbar fusion, its exact mechanism remains unclear. As an antibody to RANKL, denosumab (Dmab) effectively reduces bone resorption and stimulates bone formation, which can increase bone mineral density (BMD) and improve osteoporosis. However, it has not been confirmed whether Dmab has a reversing or retarding effect on ASDD. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…Also, tartrate-resistant acid phosphatase staining showed a significantly decreased number of active osteoclasts after denosumab treatment. 8 The in vivo response to denosumab application was assessed by these available data, which is consistent with the results of our pilot study. After considering all the factors above, we decided to use denosumab in our animal study.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Also, tartrate-resistant acid phosphatase staining showed a significantly decreased number of active osteoclasts after denosumab treatment. 8 The in vivo response to denosumab application was assessed by these available data, which is consistent with the results of our pilot study. After considering all the factors above, we decided to use denosumab in our animal study.…”
supporting
confidence: 86%
“…Moreover, denosumab treatment inhibited the expression of RANKL. 3 Sun et al 8 found that denosumab significantly increased vertebral biomechanical properties and bone mineral density. Also, tartrate-resistant acid phosphatase staining showed a significantly decreased number of active osteoclasts after denosumab treatment.…”
mentioning
confidence: 99%
“…The evidence from recent studies demonstrating the in vivo response of denosumab in rats is another factor that motivates us to use it. 2,9,12 The letter provided us with a lot of inspiration for future research and a better analysis of existing studies. According to Prof. Kostenuik's findings, the huRANKL knock-in mice, which have a human RANKL fragment encoded by the fifth exon of the RANKL gene, dramatically responded to denosumab.…”
Section: Authors' Responsementioning
confidence: 99%
“…The evidence from recent studies demonstrating the in vivo response of denosumab in rats is another factor that motivates us to use it. 2,9,12…”
mentioning
confidence: 99%
See 1 more Smart Citation